Determinan Kelaparan di Indonesia Tahun 2015-2019 - Daniel M V Mone; Efri Diah Utami (Seminar Nasional Official Statistics, 2021)
The Sustainable Development Goals (SDGs) are global action plans agreed by world leaders, including Indonesia. The purpose of this plans are to encouraging social, economic and environmental development. One of the 17 goals of SDGs is to end hunger. Based on data released by Badan Pusat Statistik, one of the approaches that use to measuring hunger level is the proportion of the population with a minimum caloric intake below 1400 kcal/capita/day is still quite high and continues to increase from 2017 to 2019. The purpose of this research is to analyze the general picture of hunger levels and the variables that are thought to influence it, and how the effect of these variables on the level of hunger in Indonesia in 2015-2019. The results of this study can be used to formulated policies for the resolution of hunger in Indonesia. The analysis method used in this research is panel data regression using fixed effect model estimated by Seemingly Unrelated Regression (SUR) method. Based on this research’s result, variables that had a significant effect on hunger levels were food expenditure and rice prices, while the number of poor people and income per capita had no significant effect to huger levels.